Hexabromocyclododecane (HBCD) induced changes in the liver proteome of eu- and hypothyroid female rats. (14th March 2016) - Miller, I.; Serchi, T.; Cambier, S.; Diepenbroek, C.; Renaut, J.; Van der Berg, J.H.J.; Kwadijk, C.; Gutleb, A.C.; Rijntjes, E.; Murk, A.J.
Graphical abstract: Highlights: Exposure of female rats to HBCD for 7 days leads to liver proteome changes. Thirty-one spots were of significantly different abundance due to HBCD exposure. Proteins with similar functions were affected in eu- and hypothyroid states. Main protein targets were in metabolic processes and oxidative stress response. Overall 150 spots varied significantly when comparing thyroid states. Abstract: Hexabromocyclododecane (HBCD) is a brominated flame retardant known for its low acute toxicity as observed in animal experiments. However, HBCD exposure can affect liver functioning and thyroid hormone (TH) status. As exact mechanisms are unknown and only limited toxicological data exists, a gel-based proteomic approach was undertaken. In a eu- and hypothyroid female rat model, rats were exposed to 3 and 30 mg/kg bw/day HBCD for 7 days via their diet, and exposure was related to a range of canonical endpoints (hormone status, body weight) available for these animals. Alterations in the liver proteome under HBCD exposure were determined in comparison with patterns of control animals, for both thyroid states. This revealed significantly changed abundance of proteins involved in metabolic processes (gluconeogenesis/glycolysis, amino acid metabolism, lipid metabolism), but also in oxidative stress responses, in both euthyroid and hypothyroid rats. The results provide a more detailed picture on the mechanisms involved in these alterations, e.g. at the protein level changes of the proposed influence of HBCD on the lipid metabolism. Present results show that proteomic approaches can provide further mechanistic insights in toxicological studies.